Influence of peak ground acceleration and soil type on seismic design of RC hotel bulding - Nur Hazwani, Mohd Rashid (2019)
In June 2015, Malaysia was shocked by a 6.0 magnitude of earthquake that had struck Ranau, one of the districts in Sabah. The moderate earthquake has broken the strongest record set in 1976, when an earthquake measuring 5.8 on the Richter scale struck Lahad Datu, causing heavy damage to property and cracks to building. Although Sabah is outside the Pacific Ring of Fire, the Centre of Research and Innovation of Universiti Malaysia Sabah, found areas in Kundasang, Ranau, Pitas, Lahad Datu and Tawau at risk of earthquakes. After been experiencing the tremors, Malaysian start to aware on the importance of seismic design on building structure. However, the consequence of seismic design application on cost of materials need to be studied beforehand. In relation to that, this study discusses on the seismic design of reinforced concrete (RC) hotel building with consideration of different magnitude of peak ground acceleration (PGA) and different soil type. The first objective of this study is to study the influence of PGA on the amount of steel reinforcement. The second objective is to analyse the effect of soil type on the amount of steel reinforcement. Ten models of hotel building with consideration of different PGA and soil type are considered, namely, non-seismic building, Soil Type B, Soil Type D, Soil Type E with PGA of 0.04g, 0.10g, 0.16g. For different magnitude of PGA, the results shows that the percentage difference of steel reinforcement required compared to non-seismic design for beam and column of the whole building had increased from 14%, 48% to 153% for PGA equals to 0.04g, 0.10g, and 0.16g respectively. While for different soil type, the results shows that the percentage difference of steel reinforcement required compared to non-seismic design had increased from 79% to 153% and reduced to 93% for Soil Type B, Soil Type D and Soil Type E respectively. Consequently, magnitude of PGA and soil type of structure give major effect to overall amount of steel reinforcement required. Thus, it is important to consider these parameter in designing a seismic building.